Pertanggungjawaban dan Mekanisme Transaksi Percetakan Stiker Perspektif Hukum Ekonomi Syariah pada Toko 57 Stic Panekan Magetan - Dio Vannesa Raka Dhani; Farchana Haryumeinanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Custom sticker printing has grown into a fast-moving niche of Indonesia's micro-enterprise sector. Late deliveries, specifications that miss the brief, and defects discovered after handover keep recurring. Toko 57 Stic in Panekan, Magetan, sits inside that pattern and serves as the case examined here. Two questions guide the inquiry. How should the shop's accountability be framed under Islamic economic law? What shape does the underlying transactional mechanism take in everyday practice? Law Number 8 of 1999 on Consumer Protection serves as the positive-law cross-reference. The design is qualitative with a normative-juridical lens, triangulating twenty-one peer-reviewed articles from 2021-2026 with the Compilation of Islamic Economic Law and DSN-MUI fatwas no. 05, 06, and 09 of 2000. Two findings emerge. Accountability sits inside the doctrine of mas'uliyyah and is exercised through the buyer's khiyar option, the duty to redo or replace, ta'widh as cash redress, and administrative or social sanction. The four routes converge on the seven-day window of Article 19 of the consumer-protection statute. The dominant contract is istishna', with ijarah 'amal for orders where customers bring their own material. Seven sequential stages anchor the contract and fence off gharar.